2008
DOI: 10.2217/17460875.3.4.453
|View full text |Cite
|
Sign up to set email alerts
|

Roles of eicosanoids in prostate cancer

Abstract: Summary Eicosanoids, the metabolites of arachidonic acid, have diverse functions in the regulation of cancer including prostate cancer. This review will provide an overview of the roles of eicosanoids and endocannabinoids and their potential as therapeutic targets for prostate cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 177 publications
(149 reference statements)
0
9
0
Order By: Relevance
“…In agreement with the reduction of the substrate arachidonic acid in PCa, it has been found that the level of their products (12-and 20-HETE, and PGE2) are higher in the tissue [36,37] and also in urine [38]. These studies along with many others have already shown that the metabolism of arachidonic acid and their products plays an important role in PCa development, and in fact, represents an important therapeutics target (reviewed in [39]). Importantly, our work suggests that the analysis of this metabolite in EVs isolated from urine samples may be used to evaluate in a non-invasive manner what is occurring in prostatic tissue itself in the context of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the reduction of the substrate arachidonic acid in PCa, it has been found that the level of their products (12-and 20-HETE, and PGE2) are higher in the tissue [36,37] and also in urine [38]. These studies along with many others have already shown that the metabolism of arachidonic acid and their products plays an important role in PCa development, and in fact, represents an important therapeutics target (reviewed in [39]). Importantly, our work suggests that the analysis of this metabolite in EVs isolated from urine samples may be used to evaluate in a non-invasive manner what is occurring in prostatic tissue itself in the context of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…The role of EP receptors in prostate cancer progression, as reviewed by Nithipatikom and Campbell [ 43 ], suggested the roles of EP2 and EP4 in tumor progression. In support, EP4 over-expression in prostatic carcinoma cells was associated with castration-resistant phenotype, and treatment with an EP4 antagonist demonstrated anti-invasive effects in vitro and halted bone metastasis in tumor-transplanted mice [ 44 ].…”
Section: Cox2/pge2 Mediated Cancer Progressionmentioning
confidence: 99%
“…Most of the LCFAs described in this study are AA precursors that in turn fuel this pathway. Eicosanoid metabolism produces a variety of molecules with reported tumorogenic activity in prostate cancer [ 42 ]. Importantly, these processes are predicted to occur in the lysosome, in which is reported that may produce pro-oncogenic alterations [ 43 ].…”
Section: Discussionmentioning
confidence: 99%